(untitled) (International Journal of Engineering and Computer Science, 2017)
Networks are Developing Continuously. The number of subscribers are increasing & new services required more network capacity. Higher capacity demands are tackled with network re-segmentation and node splitting, which leads to more effort & costly on-site re-adjustment of network devices. It will not only result in increased risk for human errors and network unreliability, but also require higher operating costs. To reduce this we require network devices which can control all errors & automatically fix these errors & monitor the whole network. For this we require Intelligent Network.